PENGARUH PENDIDIKAN DAN PELATIHAN, KEMAMPUAN TEKNIK PERSONAL DAN KETERLIBATAN PEMAKAI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI (Studi Kasus Di Universitas Muhammadiyah Metro) - Siska Nurhidayah; Yulita Zanaria; Suyanto Suyanto (Universitas Muhammadiyah Metro, 2021)
This study aims to determine the effect of education and training, personal technical skills and user involvement on the performance of the accounting information system for users of SIMAKU (financial management information system) Universitas Muhammadiyah Metro. The population in this study is SIMAKU users of every unit of Muhammadiyah Metro University with a total population of 41 users. The sampling method used in this research is total sampling (census). This study uses a quantitative approach method. The data used in this study is primary data obtained directly from research subjects in the form of a questionnaire (questionnaire) with a data measurement tool in the form of a Likert scale. The results of this study indicate that user involvement has a significant effect on the performance of accounting information systems. Meanwhile, education and training, personal technical skills have no significant effect on the performance of accounting information systems. Simultaneously education and training, personal technical skills, and user involvement have a significant effect on the performance of accounting information systems.